Genotoxic effects of mercury chloride on the Neotropical fish Andinoacara rivulatus (Cichlidae: Cichlasomatini) - Nirchio, Mauro; Choco-Veintimilla, Oscar; Fredy Quizhpe-Cordero, Patricio; Gregorio Hernandez, Jose; Oliveira, Claudio [UNESP] (Revista De Biologia Tropical, 2019)
Understanding the effects of heavy metals in aquatic ecosystems is of significant importance due to their potential to bioaccumulate at various trophic levels and induce damage in DNA. Mercury is considered one of the most dangerous heavy metals, causing chromosomal breakage (clastogenic event) or spindle dysfunction (aneugenic event), that can lead to the formation of encapsulated chromatin into a separate smaller nucleus, generally referred to as a micronucleus. We evaluated the sensitivity of the micronucleus test in the neotropical cichlid Andinoacara rivulatus (Gunther 1860). The fish were divided into four groups of 16 individuals, and each group was placed in separate aquaria (140 L) provided with filtered water and constant aeration. Fish were exposed to mercury chloride (HgCl2) at doses 0.1, 0.25, and 0.50 mg/kg body weight, administered by intraperitoneal (IP) injection. Fish from the control group were injected with a physiologic solution. The following erythrocyte anomalies were identified: erythrocytes with micronuclei varying to some extent in size and position in the cytoplasm, blebbed nucleus, binucleated cell, nuclei showing a deep invagination toward the center (notched nuclei). Examination of blood smears demonstrated a higher level of micronucleus and notched erythrocytes in fish injected with HgCl2 than in the controls. There were significant differences in the frequency of micronucleated and notched erythrocytes among the groups exposed to mercury. Linear regression analysis revealed a positive relationship between the frequency of micronucleated and notched erythrocytes (P<0.0001), with a moderately strong correlation coefficient (R=0.737). We propose that, in addition to the two so far known mechanisms of micronucleus formation (spindle apparatus damage and chromosomal ruptures), chromatin fragmentation in notched nuclei resulting from a combination of the cytotoxic effects of mercury and mechanical stress, may be a third mechanism of micronuclei genesis.
Keywords: micronuclei; erythrocyte nuclear abnormalities; DNA damage; heavy metal; fish